An Integrated Approach to Determine the Stock Structure of Spinyhead Croaker Collichthys lucidus (Sciaenidae) in Chinese Coastal Waters - Zhang, Shuai; Li, Min; Zhu, Jiangfeng; Xu, Shannan; Chen, Zuozhi (Frontiers in Marine Science, 2021)
An integrated approach including analyses of different biological traits is a proven and powerful tool used to assess the population structures offish species, which is vital for fishery stock conservation and management of wild resources. This study evaluated the use of three natural tags (microsatellites, parasites and otolith nucleus chemistry) in order to describe the populationstructure of the spinyhead croaker, Collichthys lucidus, in the coastal waters of China, on evolutionary and ecological time scales. Spinyhead croaker were assigned with 86% accuracy to their regional origin (northern China vs. southern China) using all three natural tags. Accuracy decreased when incorporating only one type of natural tag (genetics: 19%–69%; parasites: 30%–60%; otolith chemistry: 51%–86%) or when assigning the fish to a fine-scale (sea areas: 44%–64%; sampled estuaries: 19%–66%). However, the overall accuracy assignment improved slightly compared to otolith chemistry (estuaries: 55% vs. 51%; sea areas: 66% vs. 64%; regions: 86% vs. 86%). Three natural tags and integrated results show that C. lucidus in Chinese coastal waters can be separated into distinct northern and southern Chinese stocks. Finally, this information should promote the development of effective conservation strategies and integrated fisheries management plans for this commercially important species.